Interferon enhances prostacyclin production by cultured vascular endothelial cells. - Eldor, A (1984)
The effects of interferon (IFN) on the arachidonate metabolism and physiological functions of cultured endothelial cells and blood platelets have been examined. Cultured bovine aortic endothelial cells were found to be sensitive to the antiviral and antiproliferative activities of human leukocyte (alpha) IFN and to increase their capacity to synthesize prostacyclin (PGI2) upon exposure to IFN. Several observations indicate that IFN stimulates PGI2 synthesis at the level of the enzymes phospholipase A2 and cyclooxygenase: (a) PGI2 production was dependent upon the supply of exogenous arachidonic acid or the liberation of endogenous cellular arachidonate by ionophore A23187, but was not observed when IFN-treated cells were exposed to the endoperoxide prostaglandin H2. (b) IFN had no effect on the spontaneous release of PGI2 into the culture medium during the incubation period (24-72 h). (c) The stimulatory effect of IFN on PGI2 production was inhibited by both glucocorticoids and indomethacin. The effect of IFN on platelet prostaglandin metabolism was also investigated. Incubation of platelet-rich plasma with IFN had no effect on platelet aggregation and thromboxane A2 production. The biological significance of the findings presented in this paper may be considered in view of the protective role of PGI2 in the vessel wall and the fact that infection with certain viruses induces endothelial damage both in man and experimental animal models.